Analisis Sanitasi Kapal Penumpang Dengan Keberadaan Kecoa di Kapal Perintis Sabuk Nusantara 93 Pelabuhan Passarang Kabupaten Majene - Wardawati; Ahmad Rifai (Jurnal Kesehatan Nusantara (JKN), 2025)
Ship sanitation is one of the efforts shown to break the chain of disease transmission in order to maintain and increase this level. This also includes all aspects of assessing ship compartments, including: kitchen, warehouse, crew rooms, provision of clean water, provision of food and vector control. disease transmitters or rodents. Cockroaches are one of the mechanical vectors, which play a role in transmitting disease and insect cockroaches whose presence is not liked by humans. Problems that often occur related to kitchen sanitation and waste sanitation are maintaining the cleanliness of the kitchen, throwing rubbish carelessly can result in the breeding of insects/cockroaches. The aim of this research is to analyze the sanitation of passenger ships with the presence of cockroaches on the Sabuk Nusantara 93 ship. This research design uses qualitative methods. The research design used in this research is a descriptive approach. This method is carried out by combining three methods, including observation, namely by conducting direct observations on informants, in-depth interviews (in dept interviews). This research data analysis uses the Miles and Huberman model, namely data reduction, data presentation and conclusions. The results of the data analysis show that kitchen sanitation and waste sanitation have met the requirements, but there are still insects/cockroach cleaning that still needs to be carried out and there is a lack of awareness especially among passengers not to throw rubbish carelessly.